Assessment of the current condition and ontogenetic structure of the populations of Leontice incerta Pall. (Berberidaceae) in the Kyzyl-Kum Desert, Uzbekistan - NODIRJON BOBOKANDOV; ZEBUNISSO NOMOZOVA; YIGITALI TASHPULATOV; ELDOR ISOMOV; AKBAR AKHMEDOV (Society for Indonesian Biodiversity, 2024)
Abstract. Bobokandov N, Nomozova Z, Tashpulatov Y, Isomov E, Akhmedov A. 2024. Assessment of the current condition and ontogenetic structure of the populations of Leontice incerta Pall. (Berberidaceae) in the Kyzyl-Kum Desert, Uzbekistan. Biodiversitas 25: 2757-2764. The desert ecosystems of central Asia, including Uzbekistan, have a rich biodiversity and unique plant communities. High human pressure and long drought periods due to climate change have caused habitat destruction in these areas and a parallel crisis in vegetation cover. This study aimed to estimate the current population of Leontice incerta Pall., primarily distributed in the Kyzyl-Kum Desert, Uzbekistan. This focal species grew under climatic changes and human pressure in the Kyzyl-Kum Desert. The study identified five populations of L. incerta in the Kyzyl-Kum Desert. All 5 populations were estimated and measured by delta-omega and the population spectrum was determined. In the plant community, there are mostly dominated by Asteraceae (6 species), followed by Fabaceae (5 species), Amaranthaceae (4 species), Lamiaceae (4 species), Apiaceae (3 species), and other families. The plant communities consist of 49 species, including 1 species of tree, 6 species of shrubs, 6 species of semi-shrubs, 26 species of perennial herbs, and 10 species of annual herbs. The ontogenetic structure was incomplete, that is, it did not include all age groups due to biological features and harsh conditions. At all sites, the population density was low with most populations classified as young ontogenetic structures. The results will make it possible to understand estimating the current state of L. incerta. It indicated this species might, soon, become rare in the wild, therefore conservation and protection areas for this focal species are necessary.